Association of αENaC p. Ala663Thr Gene Polymorphism With Sudden Sensorineural Hearing Loss - Chen, Jialei; He, Jing; Luo, Jing; Zhong, Shixun (Frontiers in Genetics, 2021)
Abstract Objective: The etiology of sudden sensorineural hearing loss (SSNHL) is still unknown. It has been demonstrated that normal endolymph metabolism is essential for inner ear function and that epithelial sodium channels (ENaC) may play an important role in the regulation of endolymphatic Na+. This study aimed to explore the potential association between αENaC p.Ala663Thr gene polymorphism and SSNHL. Methods: Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was used to examine the genotype and allele frequency of the αENaC p.Ala663Thr polymorphism in 20 cases of low-frequency SSNHL(LF-SSNHL), 19 cases of high-frequency SSNHL(HF-SSNHL), 31 cases of all frequency SSNHL(AF-SSNHL), 42 cases of profound deafness SSNHL(PD-SSNHL), and 115 normal controls. Results: The T663 allele was found to be significantly associated with an increased risk of LF-SSNHL (P = 0.046, OR = 2.16,95% CI = 1.01-4.62). The TT genotype and T663 allele, on the other hand, conferred a protective effect for PD-SSNHL (AA vs. TT: P=0.012, OR = 0.25, 95% CI = 0.08-0.74; A vs. T: P=0.001, OR = 0.36,95% CI = 0.21-0.61). However, there was no statistically significant difference in genotype or allele frequency between the two groups (HF-SSNHL and AF-SSNHL) and the control group. Conclusion: The αENaC p.Ala663Thr gene polymorphism plays different roles in different types of SSNHL.